2016
DOI: 10.7314/apjcp.2016.17.4.2099
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Helicobacter pylori Infection and Premalignant Gastric Mucosa Using Conventional White Light Source Gastroscopy

Abstract: Background: The gold standard diagnosis of H. pylori related gastritis is evidence of bacteria on histopathological examination of gastric mucosa. Our aim was to study the correlation between gastric mucosal morphology and histopathological severity of H. pylori related gastritis. Materials and Methods: Division was made on morphological features into:Type 1, showing regular arrangement of red dots; Type 2, showing cleft-like appearance; Type 3, with a mosaic appearance; and Type 4, having a mosaic appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The Japanese school divides the status of the gastric mucosa into three categories based on endoscopic findings: normal gastric mucosa without HP infection (absence of gastritis), active HP infection (active gastritis), and previous HP infection (inactive gastritis). The endoscopic classification of Kyoto for endoscopic gastritis lists 19 endoscopic findings to characterize gastric mucosa inflammation and the presence of HP infection with high accuracy, depending on the methods used (70)(71)(72)(73)(74)(75) .…”
Section: Level Of Evidence: 1a Grade Of Recommendation: Amentioning
confidence: 99%
“…The Japanese school divides the status of the gastric mucosa into three categories based on endoscopic findings: normal gastric mucosa without HP infection (absence of gastritis), active HP infection (active gastritis), and previous HP infection (inactive gastritis). The endoscopic classification of Kyoto for endoscopic gastritis lists 19 endoscopic findings to characterize gastric mucosa inflammation and the presence of HP infection with high accuracy, depending on the methods used (70)(71)(72)(73)(74)(75) .…”
Section: Level Of Evidence: 1a Grade Of Recommendation: Amentioning
confidence: 99%
“…Although patient recruitment was prospective, analysis of the images and categorization was performed retrospectively, after the time of endoscopy. A similar classification was developed by Matrakool et al, who also demonstrated good correlation between the different endoscopic appearances and histological grade of inflammation [13].…”
Section: Authormentioning
confidence: 77%
“…A more simplified classification would be much more attractive to the less‐experienced endoscopist community who do not use IEE in their daily practice. Using conventional WLE, endoscopic morphological findings that correlate with H. pylori infection include mucosal erythema, erosions, antral nodularity, thickened gastric folds, and visible submucosal vessels . However, these findings lack reliability due to low sensitivity and specificity.…”
Section: Endoscopymentioning
confidence: 99%
“…However, these findings lack reliability due to low sensitivity and specificity. Matrakool et al . proposed an interesting simplified classification for WLE diagnosis of H. pylori infection‐related gastritis, dividing the gastric morphological features into four types: 1—regular arrangement of red dots; 2—cleft‐like appearance; 3—mosaic appearance; 4—mosaic appearance with focal or diffuse hyperemia.…”
Section: Endoscopymentioning
confidence: 99%
See 1 more Smart Citation